On a path to becoming more self-regulated: Reflective journals’ impact on Chinese English as a foreign language students’ self-regulated writing strategy use - Zhang, Yining; Li, Mingzhu; Chieh, YuanTzu; Han, Shuyuan (Frontiers in Psychology, 2022)
A number of studies have confirmed the positive effect of writing reflective journals on L2 learning. However, the relationship between writing reflective journals and the use of self-regulated writing strategies remains unclear. To redress this knowledge gap, we assigned 38 Chinese EFL students three journal-writing tasks in which they reflected on their writing processes and explored 1) the types of self-regulated writing strategies and changes to those strategies that the students’ reflective journals documented; 2) how students with varied writing-proficiency levels differed in their use of self-regulated writing strategies; and 3) the effects of reflective-journal writing on students’ self-perceived use of self-regulated writing strategies in particular, and on their L2 writing in general. Among the 19 kinds of strategies identified in 112 reflective-journal entries, only five (i.e., handling feedback, resource management, text processing, emotion regulation, and idea planning) were demonstrated relatively frequently. The use of seven strategies (i.e., self-monitoring and evaluation, idea planning, perspective change, emotional control, effort regulation, peer learning, and resource management) exhibited significant increases over time, especially during the second-half of the focal semester. In addition, our journal data highlighted individual variation in proficiency levels: with high-proficiency students significantly more likely than others to apply idea planning, feedback handling, and resource management and low-proficiency ones significantly more likely than others to engage in goal-setting. The qualitative results suggest that the practice of journaling raised students’ awareness and may have contributed to an increase in their use of self-regulated writing strategies. In particular, the findings reveal how students internalized and reconstructed the various SRL processes taking place via writing reflective journals. For L2 educators using or considering using reflective journals, these findings contain fresh insights that could help them not only to increase their students’ SRL levels, but also to provide more individualized SRL guidance.